2021
DOI: 10.1093/ibd/izab299
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine in Inflammatory Bowel Disease and COVID-19: Hospitalization and Adverse In-Hospital Outcomes Based on Nationwide Data

Abstract: Background We assessed whether 5-aminosalicylic acid (5-ASA), as treatment for inflammatory bowel disease (IBD), was associated with an increase in hospitalization for coronavirus disease 2019 and adverse in-hospital outcomes. Methods This was a Danish nationwide register study. The study population consisted of all patients with an IBD diagnosis between March 1, 2010, and March 1, 2020, and living in Denmark on March 1, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
1
0
1
Order By: Relevance
“…Lack of a dose-response relationship further supportssupports the conclusion that sulfasalazine/mesalamine are not associated with increased risk of poor COVID-19 outcomes ( Ungaro et al, 2021a , Ungaro et al, 2021b ). A population-based study of patients with ulcerative colitis (UC) in Denmark similarly found that patients treated with mesalamine/sulfasalazine had no increased risk for COVID-19-related hospitalization ( Kjeldsen et al, 2021 ). Mesalamine/sulfasalazine is safe to continue in asymptomatic and symptomatic patients with COVID-19 ( Rubin et al, 2020 ).…”
Section: Associations Between Ibd Mmedications and Covid-19 Ooutcomesmentioning
confidence: 99%
“…Lack of a dose-response relationship further supportssupports the conclusion that sulfasalazine/mesalamine are not associated with increased risk of poor COVID-19 outcomes ( Ungaro et al, 2021a , Ungaro et al, 2021b ). A population-based study of patients with ulcerative colitis (UC) in Denmark similarly found that patients treated with mesalamine/sulfasalazine had no increased risk for COVID-19-related hospitalization ( Kjeldsen et al, 2021 ). Mesalamine/sulfasalazine is safe to continue in asymptomatic and symptomatic patients with COVID-19 ( Rubin et al, 2020 ).…”
Section: Associations Between Ibd Mmedications and Covid-19 Ooutcomesmentioning
confidence: 99%
“…Erste Studien erbrachten widersprüchliche Ergebnisse hinsichtlich der Assoziation von 5-ASA mit einem schweren Erkrankungsverlauf [24,[35][36][37]. Eine kürzliche propensity score-kontrollierte Kohortenstudie zeigte hingegen, dass keine Assoziation mit einem ungünstigen Verlauf oder einer erhöhten Mortalität besteht [30].…”
Section: Leitlinieunclassified